No Smoke without Tobacco: A Global Overview of Cannabis and Tobacco Routes of Administration and Their Association with Intention to Quit - Hindocha, Chandni; Freeman, Tom P.; Ferris, Jason A.; Lynskey, Michael T.; Winstock, Adam R. (Frontiers in Psychiatry, 2016)
Cannabis and tobacco are common drugs of abuse worldwide and are often used in combination through a variety of routes of administration. Here we aimed to provide an overview of how cannabis and tobacco routes varied across countries and assess the impact of tobacco based routes of administration on motivation to use less cannabis, and less tobacco, in separate models. A cross-sectional online survey (Global Drugs Survey 2014) was completed by 33687 respondents (mean age = 27.9; %female = 25.9) who smoked cannabis at least once in the last 12 months. Most common route of administration, frequency of cannabis/tobacco use, and questions about motivation to use less cannabis/tobacco were recorded. Tobacco based routes of administration were used by 65.6% of respondents. These were most common in Europe (77.2-90.9%) and Australasia (20.7-51.6%) and uncommon in the Americas (4.4-16.0%). Vaporizer use was most common in Canada (13.2%) and the United States (11.2%). Non-tobacco based routes of administration were associated with a 10.7% increase in odds for ‘desire to use less’ tobacco (OR: 1.107, 95% CI: 1.003, 1.221), 80.6% increase in odds for ‘like help to use less tobacco’ (OR: 1.806, 95% CI: 1.556, 2.095) and a 103.9% increase in the odds for ‘planning to seek help to use less tobacco’ (OR: 2.039, 95% CI: 1.638, 2.539) in comparison to tobacco based routes of administration. Associations between route of administration and intentions to use less cannabis were inconsistent. Results support considerable global variation in cannabis and tobacco routes of administration. Tobacco routes are common, especially ‘joints with tobacco’, especially in Europe, but not in the Americas. Non-tobacco based routes are associated with increased motivation to change tobacco use. Interventions addressing tobacco and cannabis need to accommodate this finding and encourage non-tobacco routes.